2005
DOI: 10.1074/jbc.m409908200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the ρ1 GABAC Receptor Agonist Binding Pocket

Abstract: ␥-Aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the mammalian brain. The GABA receptor type C (GABA C ) is a ligand-gated ion channel with pharmacological properties distinct from the GABA A receptor. To date, only three binding domains in the recombinant 1 GABA C receptor have been recognized among six potential regions. In this report, using the substituted cysteine accessibility method, we scanned three potential regions previously unexplored in the 1 GABA C receptor, corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(122 citation statements)
references
References 31 publications
5
115
2
Order By: Relevance
“…This hypothesis is not inconsistent with the data, because we observed functional receptors with Lys, which could compensate for both of these bonding requirements, but not Ala or Asp. These data might also suggest that a positive charge is necessary for receptor function at position 170, but such a hypothesis is not supported by the results of Sedelnikova et al (5), in which a cysteine substitution yielded a functional receptor. The EC 50 for the R170C mutant was increased ϳ10-fold compared with wild type, a shift similar to that we observed for the R170K receptor.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…This hypothesis is not inconsistent with the data, because we observed functional receptors with Lys, which could compensate for both of these bonding requirements, but not Ala or Asp. These data might also suggest that a positive charge is necessary for receptor function at position 170, but such a hypothesis is not supported by the results of Sedelnikova et al (5), in which a cysteine substitution yielded a functional receptor. The EC 50 for the R170C mutant was increased ϳ10-fold compared with wild type, a shift similar to that we observed for the R170K receptor.…”
Section: Discussioncontrasting
confidence: 43%
“…Because Cys can form hydrogen bonds, it could compensate to some extent for the loss of Arg. It is not possible to tell from our data whether binding affinity or functional efficacy is being affected, but the study of Sedelnikova et al (5) indicated that this is a ligandbinding residue, because the Cys mutant at this position was protected from modification by both GABA and a competitive GABA C receptor antagonist. Further evidence comes from GABA A receptor work, where the equivalent residue (Arg-131) has been proposed to form part of a crown of arginines (in addition to Arg-207 and Arg-66) that stabilize the GABA carboxylate (16).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, molecular dynamic studies examining GABA binding to the GABA C R show that GABA appears to ' flip ' from one orientation to another during the simulation, although there is currently only experimental data to support one of the orientations (Melis et al 2008), and in silico predictions in the 5-HT 3 R have concluded that there are two possible orientations for both mCPBG and granisetron Schulte et al 2006). Comprehensive reports can be found elsewhere on the binding sites of 5-HT 3 , nACh (Romanelli et al 2007), Gly (Lynch, 2004) and GABA receptors (Abdel-Halim et al 2008 ;Huang et al 2006 ;Korpi et al 2002 ;Sedelnikova et al 2005).…”
Section: Ligand Binding : Summarymentioning
confidence: 99%
“…In the case of the ρ1 GABA C receptor, a mutation of the homologous residue (Y102S) in loop D created spontaneously opening channels [59] , further suggesting the importance of this aro- matic residue in loop D in initial conformational changes induced by an agonist. Similarly, in the ρ1 GABA C receptor, a mutation (F146C) in loop A and a mutation in loop E (Q160C) also create spontaneously opening channels [60] . Unlike AChBP, the amino-terminal domain of a cys-loop receptor is coupled to transmembrane domain.…”
Section: Activation Mechanismmentioning
confidence: 99%